2012
DOI: 10.1001/archinternmed.2012.3708
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Time and Lipid Levels in a Community-Based Population

Abstract: Fasting times showed little association with lipid subclass levels in a community-based population, which suggests that fasting for routine lipid levels is largely unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
189
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(207 citation statements)
references
References 18 publications
14
189
3
1
Order By: Relevance
“…The ability to predict the development of DM by adding TG to the model consisting of conventional risk factors significantly improved based on the area under the ROC curve in women in a non-fasting state (Table 4). In contrast, no significant differences were observed in 18) . From the view of convenience for both patients and clinicians and the need to reduce the burden on laboratories, it would be practical to use nonfasting samples 29,30) .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The ability to predict the development of DM by adding TG to the model consisting of conventional risk factors significantly improved based on the area under the ROC curve in women in a non-fasting state (Table 4). In contrast, no significant differences were observed in 18) . From the view of convenience for both patients and clinicians and the need to reduce the burden on laboratories, it would be practical to use nonfasting samples 29,30) .…”
Section: Discussionmentioning
confidence: 57%
“…Lipotoxicity, which results from the accumulation of lipids in the skeletal muscle, liver and pancreas, plays an important role in the onset of insulin resistance and β-cell damage 16,17) . Although current guidelines recommend measuring the lipid levels in a fasting state, recent studies suggest that non-fasting lipid profiles may be useful in the clinical setting 18) . The non-fasting TG levels are associated with an increased risk of cardiovascular disease 4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…It concluded that fasting times showed little association with lipid subclass levels which suggests that fasting for routine lipid levels is largely unnessecary. 29 In another prospective study, in 26,330 healthy women over an 11 year follow up period showed that except for triglycerides, lipid conc. differed minimally (<5%) for fasting vs. non fasting.…”
Section: Discussionmentioning
confidence: 94%
“…Peak non fasting TG levels four hours after a meal are reported to be a strong predictor of cardiovascular events and insulin resistance and risk equations may be developed based on these levels in the future. 28,29 Measuring non-fasting TG levels may provide additional information for determining cardiovascular risk Summary Serum Lipid profile is measured for cardiovascular risk prediction and has now become almost a routine test. The difference between fasting and non fasting values of different subclasses of lipids i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is a longstanding misunderstanding that not only TGs but also cholesterol levels are affected postprandially. Many investigators have repeatedly shown that even after an oral fat loading test, plasma cholesterol levels do not change, and this also accounts for HDL-C levels which are only minimally affected by fat ingestion (2,3). Moreover, accumulating evidence strongly supports the use of non-fasting lipids for the evaluation of cardiovascular risk (4,5).…”
Section: Introductionmentioning
confidence: 99%